2015
DOI: 10.1037/neu0000187
|View full text |Cite
|
Sign up to set email alerts
|

Movement cues aid face recognition in developmental prosopagnosia.

Abstract: Objective: Seeing a face in motion can improve face recognition in the general population, and studies of face matching indicate that people with face recognition difficulties (developmental prosopagnosia; DP) may be able to use movement cues as a supplementary strategy to help them process faces. However, the use of facial movement cues in DP has not been examined in the context of familiar face recognition. This study examined whether people with DP were better at recognizing famous faces presented in motion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 30 publications
0
37
0
Order By: Relevance
“…Although findings of a movement advantage are robust, several studies have found that movement is primarily useful when static face recognition is impaired in some way (e.g., negation, Knight and Johnston, 1997 ; blurring, Lander et al, 2001 ). Interestingly, recent research has also demonstrated that developmental prosopagnosics are able to match, recognize and learn moving faces better than static ones ( Steede et al, 2007 ; Longmore and Tree, 2013 ; Bennetts et al, 2015 ). Taken together, these findings suggest that changeable aspects of a face can constitute a useful supplementary cue for face recognition, particularly when recognition is impaired by degradation of stimuli or by perceiver impairment (also see Xiao et al, 2014 ).…”
Section: Movement and The Recognition Of Identitymentioning
confidence: 99%
“…Although findings of a movement advantage are robust, several studies have found that movement is primarily useful when static face recognition is impaired in some way (e.g., negation, Knight and Johnston, 1997 ; blurring, Lander et al, 2001 ). Interestingly, recent research has also demonstrated that developmental prosopagnosics are able to match, recognize and learn moving faces better than static ones ( Steede et al, 2007 ; Longmore and Tree, 2013 ; Bennetts et al, 2015 ). Taken together, these findings suggest that changeable aspects of a face can constitute a useful supplementary cue for face recognition, particularly when recognition is impaired by degradation of stimuli or by perceiver impairment (also see Xiao et al, 2014 ).…”
Section: Movement and The Recognition Of Identitymentioning
confidence: 99%
“…As discussed in the introduction, examination of this question in the context of an adolescent SR has particular implications for theories of the developmental course of faceprocessing, due to the proposed developmental dissociation between face perception and memory (e.g., Wiegelt et al, 2014). Thus, Experiment 3 examined OB's ability to perceive facial identity using the Cambridge Face Perception Test (CFPT; Duchaine, Germine, & Nakayama, 2007), a standardized test that has been used widely to examine face perception skills in DPs, the general population, and SRs (e.g., Bate & Cook, 2012;Bennetts et al, 2015; Bowles et al, 2009;Bobak, Bennetts, et al, 2016;Dalrymple & Palermo, 2016;Russell et al, 2009). Results: OB performed significantly better than controls on the upright trials of the CFPT, outperforming her peers by over two SDs (see Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…processing skills (e.g Bate & Cook, 2012;Bennetts, Butcher, Lander, Udale, & Bate, 2015;Dalrymple & Palermo, 2016;DeGutis, Cohan, Mercado, Wilmer & Nakayama, 2012;Herzmann, Danthiir, Schacht, Sommer & Wilhelm, 2008;McGugin, Van Gulick & Gauthier, 2016;Yang, Susilo & Duchaine, 2016),. and has demonstrated high reliability(Bowles et al, …”
mentioning
confidence: 99%
“…This could be the reason why this DP showed preserved discrimination of moving faces. Finally, in a study implementing a famous face recognition task, DPs were able to use both elastically and rigidly moving faces to their advantage when matching identities, compared to static face images ( Bennetts et al, 2015 ). These researchers concluded that DPs can learn the characteristic motion patterns for famous faces and can use them as a supplemental cue to aid recognition (SIH).…”
Section: Introductionmentioning
confidence: 99%